IMPLEMENTASI INDOOR LOCALIZATION SYSTEMDENGANZONASIBERBASIS VISIBLE LIGHTCOMMUNICATION - Muhammad Hilmy Anshoruddin; Willy Anugrah Cahyadi; Angga Rusdinar; Denny Darlis (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2021)
Industry uses autonomous mobile robots in assisting human work. However, the robot is not aware of its position within an indoor environment. Localization systems that use GPS are less effective when applied indoor. an alternative is Visible Light Communication (VLC) technology utilizing LED lights in the room. It should be noted that a localization system is quite important for knowing the position and location of the mobile robot while in operating. In this project, a localization system based on VLC zones is designed. The data used is transmitted from the LED lighting lamp to the photodiode as an identity (ID) of the lamp. The photodiode captures the light of the LED lamp containing the ID. The decoded output from the photodiode, as the receiver, is the location information displayed by nine LED indicators. The results of the experiments show that the transmitter can send information signals according to the programmed ID, i.e., zone a, b, c, d, e, f, g, h, and i. The receiver side can obtain the ID of LED with an accuracy of 80% and thus show the localized zone of the receiver. The best distance achieved between the transmitter and receiver in VLC communication is 20 to 100 cm using a 20W LED. The maximum zone range of each lamp is in the area of 32 × 32 cm2 and the receiver can identify the nine zones accordingly based on the signal sent by the transmitter.